JUMLAH PENDUDUK DKI JAKARTA BERDASARKAN KELOMPOK UMUR TAHUN 2020 - Atika Tantarani; Kendras Wiarsih, Rizka Nurbarokah, Serli Apriani, Riza Fahlapi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study aims to analyze the population in DKI Jakarta in 2020 based on sub-districts/cities and age group classification. DKI Jakarta as the capital city of Indonesia is experiencing significant population growth which has an impact on various social, economic and environmental aspects. The results of the study show that the sub-district with the highest population is in the East Jakarta area while the sub-district with the lowest population is in the Thousand Islands area. This study provides important insights into the demographic dynamics in DKI Jakarta that can be used by the government and stakeholders in formulating development and urban planning policies. Understanding the age distribution and population density in various sub-districts is essential to optimize resource allocation and infrastructure development, this study also identifies the main challenges that need to be overcome, such as inequality in population distribution and the need for adequate public facilities